Sistem Pakar dalam Mendiagnosis Penyakit Mata dengan Menggunakan Metode Forward Chaining - Budi Permana Putra; Yuhandri Yunus; Sumijan (SEULANGA SYSTEM PUBLISHER, 2021)
The eye is one of the organs in the body that has an important role in human life, because the eye is one of the organs that has a function as vision in carrying out every activity. Eye health really needs to be maintained by diligently consulting or having your eyes checked by a doctor so that vision remains clear and there are no eye problems when looking at objects around us. However, eye health is often neglected, so that many various diseases can attack the eye. If not handled properly, diseases that attack the eye can cause visual disturbances and lead to blindness. Therefore, the eye must be kept healthy and kept clean because it is a very important organ of the human body. The purpose of building this expert system is to assist the public in diagnosing eye diseases from the symptoms that are being felt. This expert system will be a way out of eye problems that are suffered by the community, In this way people no longer have trouble going to the doctor. All data and facts to be processed are obtained from an expert, the method used in diagnosing this eye disease is the forward chaining method to apply the rules of the 28 symptoms and 8 diseases described by the expert. The results of the diagnosis using the Forward Chaining method is a very good level of accuracy in determining the type of eye disease that is suffered by the community and can provide early prevention for users who use this expert system.